PENINGKATAN KEMAMPUAN MEMBACAKAN PUISI DENGAN LATIHAN TERBIMBING SISWA KELAS VIII SMP NEGERI 13 SEMARANG - Nia Ulfa Martha (LPPM Universitas Pekalongan, 2011)
This study aims to prove and know the size of the increase students’ ability to read poetry with guided exercises. This study use class action research (PTK) carried out in two stages, namely the cycle I and cycle II of SMP Negeri 13 Semarang. The variable form of the ability to read poetry and learning with guided exercises. Data collection on the first cycle and second cycle using the techniques in the form of deeds and nontest. Nontest technique used is observation. The resultshowed learning to read poetry with guided exercises to enhance students’ ability to read a poem by it self. Assessmentbased on the acquisition of appreciation, vocal technique, and appearance. In the first cycle of learning students achieve an average rating of 52.60, 72.76 secong cycle, so that an increase of 20.116. the rsult showed an increase after learning to read poetry with guided exercises performed in class action cycle I adn cycle II provides a fun learning experience and an impressive student. With the psychological state of these students, this learning can be carried out properly. Thus, the result of learning to read poetry to increase after learning to read poetry with guided exercises.This study aims to prove and know the size of the increase students’ ability to read poetry with guided exercises. This study use class action research (PTK) carried out in two stages, namely the cycle I and cycle II of SMP Negeri 13 Semarang. The variable form of the ability to read poetry and learning with guided exercises. Data collection on the first cycle and second cycle using the techniques in the form of deeds and nontest. Nontest technique used is observation. The resultshowed learning to read poetry with guided exercises to enhance students’ ability to read a poem by it self. Assessmentbased on the acquisition of appreciation, vocal technique, and appearance. In the first cycle of learning students achieve an average rating of 52.60, 72.76 secong cycle, so that an increase of 20.116. the rsult showed an increase after learning to read poetry with guided exercises performed in class action cycle I adn cycle II provides a fun learning experience and an impressive student. With the psychological state of these students, this learning can be carried out properly. Thus, the result of learning to read poetry to increase after learning to read poetry with guided exercises.